(untitled) (Revista Brasileira de Contabilidade e Gestão, 2020)
The objective of this study was to analyze the perception of the managers of a public agency in RN regarding the knowledge and procedures of the Internal Control Unit (UCI). The research is classified as quantitative, has a descriptive character, having as a technical procedure the survey type survey. Data were collected through a questionnaire, structured with 15 direct questions, reaching 78 managers. The results showed that 80% of the managers highlighted that they were unaware of the internal laws of the UCI; 75% view the ICU as a post-control body; and 83% pointed out the lack of feedback on the processes. In addition, problems related to the COSO model were found, especially regarding the control, information and communication environment, and control activities. The need to promote improvements was also highlighted, especially with regard to the management of the UCI. The research presents contributions by highlighting the need for this public agency to direct managerial strategies to solve the problems presented in its management, considering that the evidenced problems can serve as a driver to promote improvements in other UCI’s, which are part of the structures of public agencies of Brazil.